Constrictive Pericarditis Revealing Rare Case of ALH Amyloidosis With Underlying Lymphoplasmacytic Lymphoma (Waldenstrom Macroglobulinemia) - Ho, Vivian V.; O’Sullivan, Jack W.; Collins, William J.; Ozdalga, Errol; Bell, Caitlin F.; Shah, Neil D.; Krishnam, Mayil S.; Ozawa, Michael G.; Witteles, Ronald M. (JACC. Case reports, 2022)
We present a case of pericardial amyloidosis with associated lymphoplasmacytic lymphoma in a patient with chronic worsening shortness of breath and cough. This case highlights the wide variation in the presentation of cardiac amyloidosis, and the rare occurrence of clinically significant light-chain and heavy-chain amyloidosis in the pericardium. (Level of Difficulty: Advanced.) [Display omitted]